Are Earnings Management Associated With Business Strategy, Company Diversification, And Customer Concentration? - Vanda Kusuma Wijaksono; Amrie Firmansyah (Politeknik Keuangan Negara STAN, 2023)
Research objective: This study examines the effect of business strategy, company diversification, and customer concentration on earnings management. Method: The research data were obtained from www.idx.co.id, www.idnfinansial.com, and the company's official website, resulting in 148 observations from 37 companies from 2017 to 2020. The analytical method used in this research was multiple regression analysis. Research findings: The results of this study indicate that the defender-type business strategy is positively associated with earnings management, while the prospectors-type business strategy is not associated with earnings management. Furthermore, company diversification is negatively associated with earnings management, and customer concentration is not associated with earnings management. Practical implication: This research indicates that the Indonesian Financial Services Authority needs to formulate policies related to investor protection in the Indonesian capital market and to improve corporate governance policies related to the authority of managers in the company.